1997
DOI: 10.3354/meps161093
|View full text |Cite
|
Sign up to set email alerts
|

Can bacterivory alone sustain larval development in the polychaete Hydroides elegans and the barnacle Balanus amphitrite?

Abstract: Although recent studies have found that some invertebrate larvae can meet part of their metabolic needs through bacterivory, it is unclear to what extent bacterivory can compensate for reduced phytoplankton abundance. The present study determined whether larvae of a polychaete (Hydroides elegans) and a barnacle (Balanus amphitrite) can survive, grow, and develop to competence solely on a diet of bacteria. In laboratory experiments, H. eleganslarvae provided with bacteria as their sole particulate food source c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…However, a reduced larval period could lead to a reduced juvenile size (or a reduction in stored energy, as discussed above), which might have negative fitness consequences. Although such fitness consequences have been previously discussed (Strathmann 1974(Strathmann , 1977Kolding and Fenchel 1981;Perron 1986;Emlet et al 1987;Pechenik et al 1998), experimental tests are relatively rare (but see Emlet and Hoegh-Guldberg 1997;Gosselin and Qian 1997). Our results demonstrate for the first time that metamorphosis at a substantially reduced juvenile size is mechanistically possible in planktotrophic echinoid larvae (for data on lecithotrophic larvae see Okazaki and Dan 1954;Emlet and HoeghGuldberg 1997).…”
Section: Thyroid Hormones As An Indicator Of Larval Nutrition: Implicmentioning
confidence: 65%
“…However, a reduced larval period could lead to a reduced juvenile size (or a reduction in stored energy, as discussed above), which might have negative fitness consequences. Although such fitness consequences have been previously discussed (Strathmann 1974(Strathmann , 1977Kolding and Fenchel 1981;Perron 1986;Emlet et al 1987;Pechenik et al 1998), experimental tests are relatively rare (but see Emlet and Hoegh-Guldberg 1997;Gosselin and Qian 1997). Our results demonstrate for the first time that metamorphosis at a substantially reduced juvenile size is mechanistically possible in planktotrophic echinoid larvae (for data on lecithotrophic larvae see Okazaki and Dan 1954;Emlet and HoeghGuldberg 1997).…”
Section: Thyroid Hormones As An Indicator Of Larval Nutrition: Implicmentioning
confidence: 65%
“…Amphibalanus amphitrite is more microphagous in nature and is capable of feeding on phytoplankton and debris (Desai and Anil, 2004). Regarding the nutrition of this species' larvae, Gosselin and Qian (1997) observed that when bacteria concentrations were added, barnacle larvae did not grow and did not accumulate particulate material in their gut, which suggests that A. amphitrite larvae are unable to capture bacteria.…”
Section: Discussionmentioning
confidence: 91%
“…Data in parentheses are the standard deviations of 10 replicate measurements. Bacteria strain numbers correspond to the strains and properties described in Gosselin & Qian (1997) percentage of radioactivity retained in the slipper limpets, which is defined as the AE of the metals, k is the depuration rate constant, and t is time of depuration. This model assumes a 2-compartment depuration pattern for ingested metal, with the first compartment representing the digestive and assimilative process, and the second compartment representing the physiological turnover of metals.…”
Section: Methodsmentioning
confidence: 99%
“…AE and k u were determined in this study (Table 3). The mean K d values for phytoplankton were taken from Fisher & Reinfelder (1995), whereas (Gosselin & Qian 1997), and the typical seston concentration is about 1 mg l -1 (Chiu et al 1994). In modeling, we therefore used 2 × 10 6 cells ml -1 and 1 mg l -1 as representative bacterial and seston concentrations for Hong Kong waters.…”
Section: Kinetic Separation Of Metal Uptake Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation